2003
DOI: 10.1074/jbc.m300250200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2 Phosphorylates the High Mobility Group Domain Protein SSRP1, Inducing the Recognition of UV-damaged DNA

Abstract: The structure-specific recognition protein SSRP1 plays a role in transcription and replication in the chromatin context. Mediated by its C-terminal high mobility group (HMG) box domain, SSRP1 binds DNA non-sequence specifically but recognizes certain DNA structures. Using acetic acid urea polyacrylamide gel electrophoresis and mass spectrometry, we have examined the phosphorylation of maize SSRP1 by protein kinase CK2␣. The kinase phosphorylated several amino acid residues in the C-terminal part of the SSRP1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 48 publications
1
59
0
Order By: Relevance
“…Also, we found that the assembly of this ternary complex appears to be induced after UV irradiation of cells (7). Consistent with our findings is that CK2 was also shown to phosphorylate maize SSRP1 at the HMG region in vitro, and this phosphorylation seemed to induce the recognition of UV irradiation-damaged DNA by SSRP1 in vitro (21). Although SSRP1 possesses a number of CK2 consensus sites, it is still unclear which amino acids CK2 specifically phosphorylates and whether phosphorylation of these potential residues regulates the ability of SSRP1 to bind to DNA.…”
supporting
confidence: 78%
“…Also, we found that the assembly of this ternary complex appears to be induced after UV irradiation of cells (7). Consistent with our findings is that CK2 was also shown to phosphorylate maize SSRP1 at the HMG region in vitro, and this phosphorylation seemed to induce the recognition of UV irradiation-damaged DNA by SSRP1 in vitro (21). Although SSRP1 possesses a number of CK2 consensus sites, it is still unclear which amino acids CK2 specifically phosphorylates and whether phosphorylation of these potential residues regulates the ability of SSRP1 to bind to DNA.…”
supporting
confidence: 78%
“…Alternatively, SSRP1 might itself be phosphorylated (Krohn et al, 2003) to interact with ATRX-containing complex at heterochromatin. These associations, observable in vivo, suggested the formation of a multiprotein complex at the pericentromeric regions during or immediately after DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…CK2 is a ubiquitous and constitutively active Ser/Thr kinase that has Ͼ300 purported substrates identified thus far and is implicated in multiple biological processes, including cell death and survival (Litchfield, 2003;Unger et al, 2004), cellular stress responses (Yanagawa et al, 1997;Kato et al, 2003), and DNA repair and chromatin remodeling (Barz et al, 2003;Krohn et al, 2003). More than one-third of the putative substrates of CK2 are proteins involved in the regulation of gene expression (Meggio and Pinna, 2003).…”
Section: Discussionmentioning
confidence: 99%